THE CHARGE OF THE LIGHT BRIGADE And South Africa’s Very Own Pony - Usher, H.J. Dick (Scientia Militaria - South African Journal of Military Studies, 2012)
The story of the cavalry charge which I shall relate might have been forgotten by now had it not been immortalized by Alfred Lord Tennyson in his poem, ’The Charge of the Light Brigade.’ Two stanzas from that work appear in this article. The Crimean War (1853-1856) was so named because nearly all the fighting took place in the Crimea, a peninsula north of the Black Sea. Russia was a large country with few seaports. The Black Sea lies to the south of Russia, but part of the shores of the Black Sea belonged to Turkey and the Turks could keep the ships of other nations away from their shores. For this reason Russia planned to take possession of Turkey and offered to divide it, when conquered, with Britain. But Britain was not interested, and also did not want Russia to gain too much power. In the Crimean War the Allies consisted of Turkey, France, Sardinia, and Britain. The war was ended by the Treaty of Paris in 1856.